Evaluating the Suitability and Sustainability of Accounting Education Requirements from the Perspective of Employees in the Banking Sector in the Kingdom of Saudi Arabia - Adnan Oweis, Khaled (European Journal of Sustainable Development, 2025)
This study explores the perceived suitability and sustainability of accounting education among employees in Saudi Arabia’s banking sector. In light of increasing employer concerns over graduates’ readiness for the labor market, this research assesses whether current university-level accounting programs align with evolving industry needs and long-term professional demands. A structured questionnaire was administered to banking professionals holding at least a bachelor’s degree. Using Structural Equation Modeling (SEM), the study examined eight key dimensions of educational sustainability, including curriculum adequacy, instructional methods, soft skills integration, technological adoption, and experiential learning. The findings indicate that while most educational factors—particularly curriculum relevance, institutional support, and pedagogical quality—positively influence perceptions of sustainability, notable deficiencies remain in practical preparedness and the effective use of accounting information. Fit indices from Confirmatory Factor Analysis (CFA) confirm the structural soundness of the proposed model, with good-to-acceptable model fit values (e.g., RMSEA = 0.069, CFI = 0.93). Hypotheses related to curriculum adequacy, teaching quality, and technological tools were supported, highlighting their significance in shaping sustainable educational outcomes. The study emphasizes the urgent need for accounting programs to integrate dynamic, interdisciplinary, and practice-oriented learning strategies. It concludes by recommending curriculum reforms that promote ethical awareness, lifelong learning, and digital competency. These insights aim to guide academic institutions and professional bodies, such as SOCPA, in aligning accounting education with the demands of Saudi Arabia’s evolving financial sector and Vision 2030 objectives. Keywords: Accounting, Education, Efficiency and quality of accounting, Banking Sector